The role of tax-benefit systems in protecting household incomes in Latin America during the COVID-19 pandemic - David Rodriguez; H. Xavier Jara; Mariana Dondo; Cristina Arancibia Romero; David Macas Romero; Rebeca Riella; Joana Urraburu; Linda Llamas; Luis Huesca Reynoso; Javier Torres; Rodrigo Chang (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2022)
The COVID-19 pandemic drastically affected household incomes around the world. In developed economies, pre-pandemic tax-benefit policies and emergency transfers mitigated to a large extent the negative income shock. However, less is known about the effect of government intervention on household incomes in developing countries. The aim of this paper is to assess in a comparative way the role of tax-benefit policies in protecting household incomes during the pandemic in seven Latin American countries: Argentina, Bolivia, Colombia, Ecuador, Mexico, Peru, and Uruguay. Departing from previous studies, we assess the effects both of expanded social assistance programmes and of automatic stabilizers (i.e. pre-pandemic taxes and benefits). We find an important cushioning effect of emergency policies at the bottom of the pre-pandemic income distribution, whereas automatic stabilizers are mostly present at the top of the distribution as a result of reduced social insurance and tax payments during the pandemic.
Keywords: I32; I38; H24; D13; 330; taxes; benefits; COVID-19; Latin America; automatic stabilizers